Vietnamese secondary school EFL teachers' reflection on remote teaching during the Covid-19 pandemic - Châu Khánh Mai (Trường Đại học Trà Vinh, 2024)
This study generally aims to understand the significance of online teaching by exploring teachers’ reflections during the Covid-19 pandemic. Although remote instruction has been studied in depth, the research on remote education during the Covid-19 pandemic is still limited. Arguably, there is a gap in the literature examining teachers' perspectives and practices in remote teaching. The primary purpose of this qualitative study is to fill in the gap mentioned above by investigating the pedagogical strategies that secondary school EFL teachers employed and the challenges they encountered when applying these strategies.